2021
DOI: 10.1007/s11103-020-01115-7
|View full text |Cite
|
Sign up to set email alerts
|

Kleisin NSE4 of the SMC5/6 complex is necessary for DNA double strand break repair, but not for recovery from DNA damage in Physcomitrella (Physcomitrium patens)

Abstract: Structural maintenance of chromosomes (SMC) complexes are involve in cohesion, condensation and maintenance of genome stability. Based on the sensitivity of mutants to genotoxic stress the SMC5/6 complex is thought to play imminent role in DNA stabilization during repair by encircling DNA at the site of lesion by bridging the heteroduplex of SMC5 and SMC6 by non SMC kleisin components NSE1, 3 and 4. In this study, we tested how formation of the SMC5/6 circular structure affects mutant sensitivity to genotoxic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…Most SMC5/6 subunits are essential for the survival in most eukaryotic organisms, including plants (Diaz & Pecinka, 2018). Therefore, we first prepared P. patens mutant lines with reduced transcript levels using inactive dCas9 (Holá et al , 2021) to ensure their viability. We targeted the first exon of PpNSE6 with dCas9-sgRNA and obtained stably transformed lines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most SMC5/6 subunits are essential for the survival in most eukaryotic organisms, including plants (Diaz & Pecinka, 2018). Therefore, we first prepared P. patens mutant lines with reduced transcript levels using inactive dCas9 (Holá et al , 2021) to ensure their viability. We targeted the first exon of PpNSE6 with dCas9-sgRNA and obtained stably transformed lines.…”
Section: Resultsmentioning
confidence: 99%
“…Growth-response to double-strand break (DSB) damage induced by radiomimetic drug bleomycin was used for characterization of defects in DNA repair processes of Ppnse6dCas9_3 and Ppnse6KO1_47 mutant lines (Holá et al ., 2021). Consistently with the assumed role of SMC5/6 in DSB repair, Ppnse6dCas9_3 and Ppnse6KO1_47 were sensitive to bleomycin, with growth reduced to 55% and 35% of untreated controls, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…M. Holá (IEB) presented functional characterization of SMC5/6 in P. patens. Sensitivity assays revealed a critical role of SMC5/6 in double-strand-break (DSB) repair and proposed that the circularization of SMC5/6 complex by the kleisin subunit NSE4 is indispensable for the P. patens SMC5/6 function (Holá et al 2021).…”
Section: Plant Nuclei Functions and Chromatin Organization During Dna...mentioning
confidence: 99%
“…Further, Trogu et al reported the results of a multiplex gene editing technique for seven PHY genes using Multiplex CRISPR-Cas9 mutagenesis (Trogu et al 2020), and Furumizu and Sawa reported the molecular evolution of the subfamily X of Leucine-rich repeat receptor-like kinases using genomic information from a broad range of land plants, including hornworts, mosses and a liverwort (Furumizu and Sawa 2021). Studies on abiotic or biotic stress responses in P. patens include the functional analysis of the structural maintenance of chromosome protein complex, SMC5/6 complex, on DNA double strand break repair caused by genotoxic stress (Holá et al 2021), the conserved and species-specific plant defense mechanisms to a fungal pathogen using a transcriptomic approach (Reboledo et al 2021), and the comprehensive identification of small secreted peptides, some of which participate in immune responses such as to chitosan treatment (Lyapina et al 2021). Ríos-Meléndez reported the results of physiological and transcriptomic analyses of the moss Pseudocorssidium replicatum, which has high desiccation tolerance (Ríos-Meléndez et al 2021).…”
mentioning
confidence: 99%